TLR2 Arg753Gly, TLR4 Asp299Gly and Thr399Ile gene polymorphisms are not associated with chronic periodontitis in a Turkish population - Afig Berdeli (Blackwell Synergy, 2007)
Aim: Toll-like receptor (TLR) gene polymorphisms could affect the host’s ability to respond to microbial pathogens. In this case–control study, the association of TLR2 and TLR4 gene polymorphisms with chronic periodontitis (CP) was investigated. Materials and Methods: Genomic DNA was obtained from the peripheral blood of 83 patients with CP and 106 periodontally healthy subjects. The TLR2 Arg753Gly, Arg677Trp and TLR4 Asp299Gly, Thr399Ile gene polymorphisms were genotyped by the polymerase chain reaction-restriction fragment length polymorphism method. The data were analysed by a w2 test, logistic regression analysis and theMann–Whitney U test. Results: The 753Gln allele was found in 6.1% of the CP patients as compared with 6.6% in the control group (p40.05). The frequency of the 299Gly and 399Ile allele was 2.4% and 1.8% in CP patients. For the healthy subjects, the frequency was 2.8% for the 299Gly and 2.5% for the 399Ile allele (p40.05). None of the CP patients or healthy subjects showed homozygosity for the TLR2 and TLR4 alleles. Percentage of sites with bleeding on probing and plaque were significantly higher in 299Gly-positive patients compared with 299Gly-negative patients (po0.05). Conclusion: These results showed that the TLR2 and TLR4 gene polymorphisms studied are not associated with susceptibility to CP in Turkish patients.